Analisis Putusan Pengadilan Pasal 378 KUHP dan Pasal 64 KUHP dalam Dakwaan Ketiga: Studi Kasus Tindak Pidana Penipuan Berlanjut pada Putusan Perkara Nomor 490/Pid.B/2018/PN.Jkt.Pst - Afrillo, Henry; Yusuf, Hudi (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2024)
This study aims to thoroughly examine the analysis of the role of Article 378 of the Indonesian Criminal Code (KUHP) and Article 64 paragraph (1) KUHP in regulating and addressing the continued criminal act of fraud. The main concentration of the research revolves around court decisions related to the cases of Porman Tambunan and Donny Andy Sarmedi Saragih. The research employs a normative legal research method adopting a case study approach. Article 378 of the Indonesian Criminal Code serves as a detailed guide in handling the ongoing criminal act of fraud, especially when combined with Article 64 paragraph (1) KUHP. The simultaneous application of these two articles is designed to provide a significant deterrent effect on perpetrators and ensure robust legal protection for the public. In the context of the case under study, the court decisions affirm the suitability of the punishment demands with the provisions stipulated in Article 378 KUHP and Article 64 paragraph (1) KUHP. The research also discusses the effectiveness of Article 64 paragraph (1) KUHP in the aspects of prevention, punishment, and recovery of losses in cases of ongoing fraud. The heavier penalties under these provisions have proven to be an effective instrument in preventing fraudulent activities and achieving the expected deterrent effect. The cases of Porman Tambunan and Donny Andy Sarmedi Saragih provide evidence that the application of these articles has successfully created a preventive legal system and significant deterrence. Through in-depth analysis of court decisions, this research presents a more comprehensive insight into the role and effectiveness of Article 378 KUHP and Article 64 paragraph (1) KUHP in addressing the challenges of ongoing fraudulent activities. The outcomes of this study are anticipated to enhance comprehension of legal aspects of applications in upholding justice, especially in cases of fraud involving ongoing elements.